Analysis of the Problems of Educational Institutions and the Role of Education Personnel in Realizing A Conducive Learning Environment - Titis Istiqomah (CV. Get Press Indonesia, 2025)
A conducive learning environment is a key factor in supporting the success of the educational process within schools. However, internal challenges often hinder the creation of an ideal atmosphere. This study aims to analyze the problems faced by educational institutions and explore the strategic role of educational personnel in fostering a conducive learning environment. A descriptive qualitative approach was employed, involving participatory observation, in-depth interviews with 12 informants (educational personnel, teachers, and school leaders), and document analysis at two public secondary schools over a three-month period. The results showed that major challenges include ineffective management, weak coordination among staff, and inadequate support facilities. Educational personnel serve as mediators and facilitators in strengthening communication, ensuring order, and supporting the learning process through infrastructure management. These findings highlight the urgent need to enhance the capacity and professionalism of educational personnel through targeted training and empowerment programs. In conclusion, the active involvement of educational personnel is crucial in overcoming institutional challenges and enhancing a learning environment that promotes student achievement.